Pelatihan Kognitif Perilaku Untuk Menurunkan Tingkat Depresi Pada Penerima Manfaat Di Balai Rehabilitasi Sosial Wanita Utama Surakarta - Jeprina, Tiya, Dr. Nisa Rachmah N.A., M.Si., Psikolog, Rini Lestari, M.Si (2016)
Singer study aims to determine the effectiveness of review cognitive behavior training provision for review lowers level of depression the recipient benefits in social rehabilitation center "wanita utama" surakarta. Research experiment singer model using quasi-experimental designs shaped pre-test-post test control group design with cognitive training interventions behavior. Singer research subjects totaling 16 recipients the benefits are divided become prayer namely group 8 recipients benefits perimental group and the control group 8 suffered moderate depression and high level. Data analysis using n-parametric test engineering k related samples and mann whitney u test. The difference in test results score pre test, post-test and follow up shows that cognitive training interventions behavior showed significant differences before the awarded experimental group intervention and intervention given taxable income. It was concluded that cognitive training interventions behavior has contributed significantly operates hearts to give change decline against the recipient benefits degree of depression.